2022
DOI: 10.1021/acs.langmuir.2c02332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HKUST-1 as Volatile Organic Compound Adsorbents for Respiratory Filters

Abstract: Cyclohexane is a representative of volatile organic compounds (VOCs). VOCs can cause serious health problems in case of continuous exposure; therefore, it is essential to develop efficient personal protective equipment. Historically, activated carbons are used as VOC adsorbents. However, the emergence of promising novel adsorbents, such as metal–organic frameworks, has pushed the research to study their behavior under the same conditions. In this work, the use of the well-known HKUST-1 MOF of different particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The characteristics of the reduced column and the operating conditions are listed in Table . Although the particle diameter to column diameter ratio (δ = D c / d pe ) is relatively low, which may lead to preferential flow paths and nonuniform flow, it is worth noting that this column diameter is not uncommon in the literature and has been used in previous studies. , In addition, we are aware of the potential for preferential flow paths in our study and have attempted to address this issue by careful packing of the adsorbent bed and a relatively low flow rate. A recent study by Petrazzuoli et al showed that preferential pathways through the wall can occur when the value of δ (column-to-sphere diameter ratio) is less than 1.78, whereas in our study, the value of δ is between 2 and 2.7.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…The characteristics of the reduced column and the operating conditions are listed in Table . Although the particle diameter to column diameter ratio (δ = D c / d pe ) is relatively low, which may lead to preferential flow paths and nonuniform flow, it is worth noting that this column diameter is not uncommon in the literature and has been used in previous studies. , In addition, we are aware of the potential for preferential flow paths in our study and have attempted to address this issue by careful packing of the adsorbent bed and a relatively low flow rate. A recent study by Petrazzuoli et al showed that preferential pathways through the wall can occur when the value of δ (column-to-sphere diameter ratio) is less than 1.78, whereas in our study, the value of δ is between 2 and 2.7.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) possess unique properties that include high specific surface area, flexible structures, open metal sites, and high thermal stability, which explain their prospective use in gas storage and separation, adsorption, and many other fields. , Benefiting from a large specific surface area, high porosity, low density, structural variability, and chemical stability, MOFs are widely regarded as very promising adsorbents . However, in practical applications, MOFs exhibit some technical limitations such as particle agglomeration and difficulty in recycling .…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Benefiting from a large specific surface area, high porosity, low density, structural variability, and chemical stability, MOFs are widely regarded as very promising adsorbents. 31 However, in practical applications, MOFs exhibit some technical limitations such as particle agglomeration and difficulty in recycling. 32 On the other hand, biopolymers such as cellulose fiber have good processability, softness, heat and weather resistance, 33 and chemical stability, 34 in addition to various surface functional groups to anchor metal ions or participate in intermolecular interactions with guest molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At the same time, the air pollution evaluation index of SO 2 was replaced by VOCs in the 14th Five-Year Plan (2021–2025) for National Economic and Social Development and Vision 2035 of the People’s Republic of China. Therefore, a lot of VOCs control technologies such as thermal oxidization, catalytic oxidization, , absorption, condensation, , and adsorption , were developed. Currently, the adsorption technology is reported as the most promising VOCs control technology due to its low operation cost, convenient operation, and high removal efficiency. , …”
Section: Introductionmentioning
confidence: 99%